Emergency Department Workflow Times of Intravenous Thrombolysis with Tenecteplase versus Alteplase in Acute Ischemic Stroke: A Prospective Cohort Study before and during the COVID-19 Pandemic - Matias Guzman; Pablo M. Lavados; Gabriel Cavada; Alejandro M. Brunser; Veronica V. Olavarria (Cerebrovascular Diseases Extra)
Introduction: Tenecteplase (TNK) has demonstrated to be non-inferior to alteplase (ALT) for intravenous thrombolysis (IVT) in acute ischemic stroke (AIS). There are potential workflow benefits associated with TNK use, aiming to reduce patient length of stay in the emergency department. Our aim was to investigate whether the routine use of TNK during the COVID-19 pandemic influenced workflow times compared to historical use of ALT, while maintaining non-inferior clinical outcomes in a non-drip and ship scenario of a comprehensive stroke center. Methods: We included patients with AIS admitted from September 2019 to September 2022 and compared those treated with TNK during the COVID-19 pandemic to those treated with ALT in the period immediately before. We compared emergency department length of stay (EDLOS), door-to-needle time (DTN), door-to-groin puncture time (DTG), clinical and safety outcomes with adjusted general linear regression models. Results: 110 patients treated with TNK and 111 with ALT were included in this study. Mean EDLOS was 251 (SD = 164) min for TNK users versus 240 (SD = 148) min for ALT (p = 0.62). Mean DTN was 43 (SD = 25) min for TNK versus 46 (SD = 27) min for ALT users (p = 0.39). Mean DTN under 60 min was achieved in 86 (78.2%) patients and in 85 (76.5%) patients of the TNK and ALT groups, respectively (p = 1.0). DTN under 45 min was achieved in 65.4% and 58.6% (p = 0.65) of the TNK and ALT groups, respectively. DTG time was 114 (SD = 43) min for TNK versus 111 (58 = SD) min in the ALT group (p = 0.88). DTG under 90 min was achieved in 32% of the TNK group and 35% of the ALT group (p = 0.69). There were no differences in any of the clinical or safety outcomes between groups at 90 days. Conclusions: The adoption of TNK during COVID-19 pandemic did not result in a change in EDLOS, DTN, or DTG times when compared to ALT in this cohort. Safety and clinical outcomes were similar between groups. Probably a greater benefit could have been seen in a drip and ship thrombolysis setting. Further research is needed to assess the potential advantages of TNK in drip and ship scenarios of IVT.